Al-Qur'an Literacy in Building Nation's Civilization: Universal Values Study - Aziz, Husein (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This research is intended to present the universal values of the Qur’an in building civilization, especially in social interactions within the nation and state. This research is motivated by social phenomena prone to upheaval, dissolution, and violence due to differences in ideology, politics, class, ethnicity and race, and religious beliefs. Research is focused on the problem, 1. moral decadence in all lines of social life due to a crisis of values. 2 causes of value crisis. 3. The universal values of the Qur’an answer these crisesThis study uses the method of library research and content analysis, and phenomenology. The data is taken from the Qur’an and the interpretation of the Qur’an, classics such as the interpretation of al-Tabary, medieval interpretations such as Ibn Kathir, and modern interpretations such as the interpretation of al Wadih.The findings of this study are: a. Moral decline in social life is caused by a crisis of values. b. value crisis caused by a crisis of thought and education. c. The universal values of the Qur’an can create social stability and a sense of security, eliminating family barriers, ethnicity, race, and religious beliefs. Conversely, ignoring the universal values of the Qur’an will result in chaos, violence, weakness, crime, and vulnerability to the destruction of a nation.